La intolerancia a la lactosa en la práctica clínica - Garrido-Klinge, German (1972)
Reviewing 800 consecutive clinical histories of gastroenterological private practice, 130 cases consulted mainly for flatulence, gas sensation, abdominal dilatation, diarrhea tendency and intestinal noises. In this, group lactose and glucose tolerance test (LTT-GTT) were made, founding that 56% had a flat LTT. The importance of this deffect as the only source of symptoms or agravating agent associated to other pathology is emphasized. The relationship between lactose intolerance and emotional disturbances is pointed out.